Social technologies and solid waste: cataloging experiences in cooperatives and associations of recyclable materials collectors and a portrait of the Brazilian Amazon (Research, Society and Development, 2022)
This study aimed to build a regionalized analytical matrix of Brazilian experiences in Social Technologies (TS) within the scope of cooperatives and associations of recyclable material collectors, highlighting the Amazonian reality observed from the constructed matrix. Therefore, data collection was performed using keywords in two databases: Fundação Banco do Brasil (FBB) and Google Scholar (Google Scholar). Of the total of investigated STs, it was identified that 17 were developed by, or in conjunction with, cooperatives/associations. The main obstacles identified for the implementation of STs, or during the process, were related to four axes: economic, environmental, institutional and social. Regarding the main advances that the cataloged TS have achieved are: the formalization of cooperatives; the training of the workers involved; development of composting programs; community mobilization; optimization of collection and recycling processes; implementation/expansion of selective collection; correct disposal of waste; improvement in the quality of life and significant increase in the cooperative members' income. Regarding the Brazilian Amazon, of the 17 TS catalogued, only three experiences are located in the region (approximately 18% of the total). The low percentages of SW identified in the Amazon reveal the proven inefficiency in the strategic integration of different actors: State, private organizations and community. This integration is extremely important for the efficiency in the development and application of ST that provide real benefits for the population involved.